Ivabradine versus carvedilol in the management of palpitation with sinus tachycardia among recovered COVID-19 patients - Jadhav, Kartik Pandurang; Jariwala, Pankaj V (Journal of Cardiology and Cardiovascular Medicine, 2020)
Introduction: One of the major complications among COVID-19 patients include cardiac arrhythmias. Commonest arrhythmia is sinus tachycardia which is usually associated with palpitation causing discomfort to patients. In this study, we present a comparative study of use of Ivabradine vs. Carvedilol for sinus tachycardia in post-COVID-19 infected patients. Method: 50 consecutive recovered COVID-19 patients with sinus tachycardia were included in this open labelled RCT. 25 patients received Ivabradine and remaining 25 received Carvedilol. Single therapy non-responders were treated with Ivabradine with Atorvastatin. Results: The mean age of all patients is 48.8±7.66 years (Males 49.5 ± 7.21 years; Females 47.68 ± 8.23 years). The mean heart rate (MHR) of all patients is 125.52 ± 9.07/min (Males 125.67 ± 8.78/min; Females 125.26 ± 9.5/min). After five days of single drug therapy the mean drop in the heart rate was 35.04 ± 10.55/min (Males 34.41 ± 9.71/min; Females 36.05 ± 11.72/min), resulting in 27.88 ± 8.11% (Males 27.38 ± 7.56%; Females 28.69 ± 8.89%) reduction in MHR. Among the two groups, the Carvedilol group showed improvement of MHR in 14(56%) patients; whereas in Ivabradine group 18(72%) patients improved out of 25 patients each (p: 0.2385). In the Carvedilol group the MHR reduced from 128.6 ± 8.44 to 95.68 ± 10.63 (p < 0.001), which is statistically significant; similarly, the Ivabradine group showed a MHR from 122.44 ± 8.62 to 85.28 ± 10.52 (p < 0.001). The monotherapy therapy non-responders were treated with dual-therapy of (Ivabradine + Atorvastatin). Discussion: Ivabradine is more effective in controlling heart rate compared to Carvedilol. Also, Ivabradine group scores very well in ‘patient-satisfaction’ with regards to symptom (palpitation) relief. Conclusion: The COVID-19 sequelae of sinus tachycardia can be better controlled with Ivabradine when compared to Carvedilol.